Osteoking promotes bone formation and bone defect repair through ZBP1-STAT1-PKR-MLKL-mediated necroptosis - Suya Zhang; Yudong Liu; Zhaochen Ma; Shuangrong Gao; Lin Chen; Honggang Zhong; Chu Zhang; Tao Li; Weiheng Chen; Yanqiong Zhang; Na Lin (BMC, 2024)
Abstract Background Osteoking has been used for fracture therapy with a satisfying clinical efficacy. However, its therapeutic properties and the underlying mechanisms remain elusive. Method A bone defect rat model was established to evaluate the pharmacological effects of Osteoking by the dynamic observation of X-ray, micro-CT and histopathologic examination. Transcriptome profiling was performed to identify bone defect-related genes and Osteoking effective targets. Then, a "disease-related gene-drug target" interaction network was constructed and a list of key network targets were screened, which were experimentally verified. Results Osteoking effectively promoted bone defect repair in rats by accelerating the repair of cortical bone and the growth of trabeculae. Histopathologically, the bone defect rats displayed lower histopathologic scores in cortical bone, cancellous bone and bone connection than normal controls. In contrast, Osteoking exerted a favorable effect with a dose-dependent manner. The abnormal serum levels of bone turnover markers, bone growth factors and bone metabolism-related biochemical indexes in bone defect rats were also reversed by Osteoking treatment. Following the transcriptome-based network investigation, we hypothesized that osteoking might attenuate the levels of ZBP1-STAT1-PKR-MLKL-mediated necroptosis involved into bone defect. Experimentally, the expression levels of ZBP1, STAT1, PKR and the hallmark inflammatory cytokines for the end of necroptosis were distinctly elevated in bone defect rats, but were all effectively reversed by Osteoking treatment, which were also suppressed the activities of RIPK1, RIPK3 and MLKL in bone tissue supernatants. Conclusions Osteoking may promote bone formation and bone defect repair by regulating ZBP1-STAT1-PKR axis, leading to inhibit RIPK1/RIPK3/MLKL activation-mediated necroptosis.